Desenvolvimento de banhos alcalinos para eletrodeposição de Pb-Sn e Pb-Cu, na presença de aditivo orgânico. Caracterização do processo de eletrodeposição e dos filmes - Siqueira, Joana Luiza Pires (2007)
Alkaline baths containing sorbitol, tartrate or EDTA were developed in this work for Pb-Sn and Pb-Cu electrodeposition on platinum substrate. The characterization of Pb-Sn and Pb-Cu plating baths by potentiometric titration showed the pH when the species of metallic ions were soluble and stable. The voltammetric curves obtained from these baths indicated that the complexation of metallic ions by sorbitol, tartrate or EDTA, had a beneficial effect, since closed the deposition potential these metallic ions, leading to codeposition of Pb-Sn and Pb-Cu. The analysis of the Pb-Sn and Pb-Cu deposits by x-ray dispersive spectroscopy showed that codeposition of Pb-Sn or Pb-Cu occurred. The codeposition type of Pb-Sn was normal irrespective the additive in the plating bath; the coloration of the films was bright gray and the morphology was formed of refined crystallites. For Pb-Cu alloy the codeposition type was anomalous to the deposits obtained from baths containing sorbitol or tartrate and normal in the presence EDTA. The Pb-Cu deposits obtained in the presence of sorbitol, EDTA or tartrate showed black coloration; or coloration varying of brown to redish or golden to dark redish, respectively. X ray diffraction spectroscopy of the Pb-Sn and Pb-Cu codeposits indicated that these were to constitute a mixture of compounds.